3(7+2x)=5(2x+4x)

Simple and best practice solution for 3(7+2x)=5(2x+4x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(7+2x)=5(2x+4x) equation:


Simplifying
3(7 + 2x) = 5(2x + 4x)
(7 * 3 + 2x * 3) = 5(2x + 4x)
(21 + 6x) = 5(2x + 4x)

Combine like terms: 2x + 4x = 6x
21 + 6x = 5(6x)

Remove parenthesis around (6x)
21 + 6x = 5 * 6x

Multiply 5 * 6
21 + 6x = 30x

Solving
21 + 6x = 30x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-30x' to each side of the equation.
21 + 6x + -30x = 30x + -30x

Combine like terms: 6x + -30x = -24x
21 + -24x = 30x + -30x

Combine like terms: 30x + -30x = 0
21 + -24x = 0

Add '-21' to each side of the equation.
21 + -21 + -24x = 0 + -21

Combine like terms: 21 + -21 = 0
0 + -24x = 0 + -21
-24x = 0 + -21

Combine like terms: 0 + -21 = -21
-24x = -21

Divide each side by '-24'.
x = 0.875

Simplifying
x = 0.875

See similar equations:

| 2x-3y=3x+8y | | -16+4x-7x=5-6x | | a-(b-(c+d))= | | 12p-(5+2p)= | | -6(5k+4)=-144 | | (2x-3)(2x-3)(2x-3)= | | 62x+44+2x=-20 | | (3x+y)(3x+y)(3x+y)= | | 2x-x-14=0 | | 125x^6+27y^3= | | (3*3*3*3)-79=2 | | 3x^2-79=2 | | (x-5)(x+8)=10 | | (2x^2+3)+(4x^3+1)= | | y=x^4tan(5x) | | (X+y)-6x+8y= | | 2-x=x^2 | | (X+y)-2(3x-4y+3)= | | 5k-3(b+3k)-3b= | | a+3(2a-3b+c)+7c= | | P=3m+21 | | 3(5x-4y)-2(x-4y)= | | cos(2x)-sen(2x)=senx | | 2[x+4]=20 | | x^3+4x^2-4x=0 | | 6x-5=64x^2-112x+49 | | 6x-5=64x-112x+49 | | 5x(a-6b+5c)-2x(b-c)= | | 64x^2+105x+56=0 | | 1/2-x*1/2=1/8 | | 12-x=1/8 | | 14.2=7x-3.3 |

Equations solver categories